THE EFFECT OF PERFORMANCE ALLOWANCES ON EMPLOYEE MORALE AT THE REPRESENTATIVE OF THE NATIONAL POPULATION AND FAMILY PLANNING AGENCY (BKKBN) OF THE SPECIAL REGION OF YOGYAKARTA - Muhammad Isnaini Fathoni; Kuswanto Kuswanto; Herman Wahyu Dwi Maelana (Universitas Islam Lamongan, 2022)
This study aims to determine the effect of performance allowances on employee morale at the Representative of the National Population and Family Planning Agency (BKKBN) of the Special Region of Yogyakarta. The population in this study amounted to 98 people, while the sample in this study amounted to 79 people. The results of this study shows that the magnitude of the influence of performance allowances on employee morale at the Representative of the National Population and Family Planning Agency (BKKBN) of the Special Region of Yogyakarta. is 2.6%, while the remaining 97.4% is influenced by other variables or factors.